2018
DOI: 10.1002/2017sw001767
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Magnetic Structure of Earthbound CMEs and In Situ Comparison

Abstract: Predicting the magnetic field within an Earth‐directed coronal mass ejection (CME) well before its arrival at Earth is one of the most important issues in space weather research. In this article, we compare the intrinsic flux rope type, that is, the CME orientation and handedness during eruption, with the in situ flux rope type for 20 CME events that have been uniquely linked from Sun to Earth through heliospheric imaging. Our study shows that the intrinsic flux rope type can be estimated for CMEs originating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 129 publications
(192 reference statements)
6
71
0
Order By: Relevance
“…In order to further confirm the CME-ICME associations described above, we compare the helicity sign of the corresponding flux ropes at the Sun with the magnetic structures in situ. At the Sun, we use proxies from multiwavelength observations (e.g., Palmerio et al 2017Palmerio et al , 2018; at 1 AU, we apply the Gold-Hoyle flux rope fitting technique (Gold & Hoyle 1960;Farrugia et al 1999), shown in Figure 5 at both spacecraft. We note clear reverse-J flare ribbons after the eruption of both CME3 and CME4, which are a sign of negative helicity.…”
Section: Dst [Nt]mentioning
confidence: 99%
“…In order to further confirm the CME-ICME associations described above, we compare the helicity sign of the corresponding flux ropes at the Sun with the magnetic structures in situ. At the Sun, we use proxies from multiwavelength observations (e.g., Palmerio et al 2017Palmerio et al , 2018; at 1 AU, we apply the Gold-Hoyle flux rope fitting technique (Gold & Hoyle 1960;Farrugia et al 1999), shown in Figure 5 at both spacecraft. We note clear reverse-J flare ribbons after the eruption of both CME3 and CME4, which are a sign of negative helicity.…”
Section: Dst [Nt]mentioning
confidence: 99%
“…The figure also shows the magnetic structure of the flux rope propagating towards the observer in the ecliptic plane-the configuration of most halo-CME eruptions that impact the Earth and cause significant geomagnetic responses (Zhang et al 2007). Understanding this connection between the preeruption magnetic configuration of the CME source region and the CME's structure and evolution during the eruption and propagation through the heliosphere is of critical importance to terrestrial space-weather forecasting (Palmerio et al 2018) and will play an increasingly important role in characterizing exoplanetary space weather (Airapetian et al 2016b;Cohen et al 2018). Figure 7 plots the evolution of the global magnetic energy (E M , black) and kinetic energy (E K , red).…”
Section: Carrington-scale Eruptive Stellar Flare and Cmementioning
confidence: 99%
“…The red line shows the shock and the interplanetary Coronal Mass Ejection flux rope is between the pair of blue lines. The schematic on right (from Palmerio et al, ) illustrates the local variations of the magnetic field around the axis of the flux rope.…”
Section: Coronal Mass Ejections Close To the Sun And In Interplanetarmentioning
confidence: 99%
“…While less dramatic, rotations and deflections in interplanetary space cannot be ignored. They can still change significantly the orientation and direction of the flux rope and for some cases even dominate the total change (e.g., Isavnin et al, ; Palmerio et al, ). For example, Good and Forsyth () reported a case where a flux rope rotated by several tens of degrees while it propagated from Mercury to radially aligned STEREO‐B near 1 AU.…”
Section: Physical Aspects Of Cmesmentioning
confidence: 99%
See 1 more Smart Citation